Evaluation of Tween 80 incorporated media to increase pathogen isolation from peritoneal fluid of CAPD patients at Hospital Kuala Lumpur - Ganapathy Pillay, Stella; Mohd Amin, Sofia Duratul Waheda; Masri, Siti Norbaya; Sither Joseph Vesudian, Narcisse Mary; Amran, Fairuz; Van Belkum, Alex; Amin Nordin, Syafinaz (Malaysian Society of Pathologists, 2021)
Introduction: Continuous ambulatory peritoneal dialysis (CAPD)-associated peritonitis remains a major complication in patients on CAPD leading to increased morbidity and mortality. Successful therapy of peritonitis is highly dependent on a positive microbiological culture because narrow spectrum antibiotics are essential to efficiently combat infection. Therefore, this study evaluated the performance of Tween 80 containing media at three different concentrations (0.1%, 1.0% and 2.0%) to increase the pathogen yield from peritoneal fluid in comparison with the standard culture media. Materials and methods: Peritoneal fluid samples (n=121) obtained from CAPD patients suspected of peritonitis at Hospital Kuala Lumpur were analysed macroscopically and microscopically prior to culture. All samples were cultured on seven different culture media, including sheep blood agar, MacConkey agar, Sabouraud dextrose agar, brain heart infusion agar and Tween 80 incorporated blood agar. All plates were incubated at an optimum temperature up to 48 hours. Results and conclusion: Among all the culture media investigated, 0.1% to 2.0% Tween 80 incorporated blood agar yielded the highest positive culture (23/121) in comparison with all other standard media, thus lowering the negative culture rate among CAPD patients. Statistical analysis by Chi Square revealed significant differences (p <0.001) between the three concentrations of Tween 80 tested in this study. Among the three different concentrations of Tween 80 optimised in this study, blood agar containing 0.1% Tween 80 generated the best results, achieved by optimum growth of all Gram-positive organisms, Gram-negative organisms and yeast cells simultaneously. Using a small amount of detergent at low cost significantly increased the pathogen yield during CAPD-associated peritonitis.